Efeitos dos exercícios/terapias mente e corpo sobre a saúde mental e cognitiva do idoso - OLIVEIRA, Jhonatta Marcos Torres de (2021)
Objective: The preserved mental and cognitive health is fundamental for quality of life and functional autonomy in the aged population. An active lifestyle and the practice of mind-body exercises can improve the age-related cognitive decline, aspects of mental health and quality of the aging population. Method: An integrative literature review was performed on PubMED, Cochrane and Scopus databases. The following descriptors and their combinations were used: “mind-body exercises”, “mental health”, cognition and aging. Inclusion criteria: a) full text availability; b) older adults as study participants, having as intervention some sort of mind-body exercise or systematic reviews and / or meta analysis of experimental studies on the subject; c) cognition or mental health as outcomes; d) articles published in the last 10 years (2010-2020). Results: Mind-body exercises cover a range of practices such as Pilates, Yoga, Tai-chi and Mindfulness each with particularities that adapt to specific demands of older adults. If practiced regularly, Mind-body exercises can improve quality of life, prevent declines or improve aspects of mental and cognitive health in aging, contributing to the preserved autonomy and independence to perform daily life activities on aging. Conclusion: To introduce a mind-body exercise in daily living can be a safe and effective way to maintain older adults’ mental and cognitive health, having in its scope a wide variety of practices, philosophies and martial arts that can adjust to personal preferences and pleasure of its practitioners. However, despite its benefits and safety find scientific support, there is a need for studies with a larger sample and appropriated methodological design to address long-term practice effects and the underlie anatomophysiological mechanisms.